Tahsin Tracker as an Effort to Improve the Services of the Islamic Studies Development Institute for Lecturers and Education Personnel at Ahmad Dahlan University - Tarmuji, Ali; Masduki, Yusron (Jurusan Informatika, 2024)
Purpose: This research aims to produce a Tahsin Tracker application as a tool to overcome several problems in managing tahsin guidance organized by the Islamic Studies and Development Institute (LPSI) UAD for lecturers and education staff.Design/method/approach: The method used in system development by applying general software development methods. The stages adopted include data collection, needs analysis (user and system), design (process, database and interface), implementation (database and program, and system testing.Results: A Mobile Web-based Tahsin Tracker application has been produced and has been tested on potential users using black box and SUS testing. Black box testing is 100% valid. The SUS test obtained a score of 79. Based on the SUS score of 79, the application is in the Acceptance Range: ACCEPTABLE, Grade Scale: C, and Adjective Rating: EXCELLENT category.Originality/state of the art: Based on previous research, as well as the results of the development of existing tahsin applications, this research adopts and complements existing deficiencies and produces new assessments of the features and usability in related units, because it replaces the manual method of book record basis, and becomes the main alternative for developing institutional service media in a better direction.